Adolescent Fat Embolism Syndrome after Closed Tibial Shaft Fracture: Treatment with Emergent External Fixation - Dillon C. O’Neill; Graham J. Dekeyser; Alexander J. Mortensen; Christopher A. Makarewich (Case Reports in Orthopedics)
Case. An adolescent male developed fat embolism syndrome 24 hours after sustaining a closed right tibial shaft fracture in a football game. The patient was treated with emergent external fixator application due to declining respiratory and mental status and experienced swift recovery after stabilization. He was treated with an intramedullary nail within 1 week of injury. Conclusion. Pediatric fat embolism syndrome is uncommon, and a high index of suspicion is required to facilitate appropriate orthopaedic involvement. External fixation can be performed emergently with minimal fracture manipulation. Rapid provisional fixation appears to have facilitated recovery in this example.